The image of a contemporary in Azilkhan Nurshaikov’s epistolary journalism - Shaikenova, А.Ж.; Tulesheva, Г.К.; Umbetova, А.К. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2025)
This scientific article is devoted to the epistolary heritage of Azilkhan Nurshaikov. The reflection of humans sence through letters occupies a special place in the author's work and literary heritage. The main purpose of the research is to study Azilkhan Nurshaikov's letters and determine his role and significance inrevealing humans sence and personal qualities. An important direction of scientific research is a comprehensive study of epistolary journalism in the context of the development of Kazakh literature, tracing its close relationship with national literature. In addition, the analys is of the author's personal life and views in letters reveals the deep meaning and ideas of his works. The practical significance of the study lies in assessing the artistic value of A. Nurshaikov’s letters from the point of view of the development of modern journalism and in ensuring that research in this area becomes the basis for future scientific work. Based on the research, the content and stylistic features of A. Nurshaikov's letters are analyzed. Philosophical thoughts and issues of inter personal relations in letters are considered, and a special view of the author's work is formed. In addition, the article discusses the possibility of understanding the inner world of a person through letters, revealing his complex psychology. This study reveals the depth and versatility of A. Nurshaikov’s spiritual heritage and contributes to strength ening his place in Kazakh journalism. In addition, the result soft he work have practical application in the field of Kazakh journalism and publicism, strength ening the basis of new scientific views and research methods. In particular, the role and significance of the author's epistolary heritage in the modern mediaspace are considered.